Exploration of Financial Statements CV. Wian Mandiri Based on Financial Accounting Standards for Micro, Small, and Medium Entities - Dimas Wahyu Darmawan; Nina Martiana; Diyah Probowulan (Westscience Press, 2024)
The title of the research is